Correlation between Academic Sports Diplomacy Ability and Leadership Quality of Student Athletes in Universities - Gong, Xiaoming; Chang, Liza; Dapat, Rizal (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
This research investigates the field of academic sports diplomacy, with a specific emphasis on the leadership abilities and levels of involvement exhibited by student-athletes. By conducting a thorough analysis, this study reveals valuable insights regarding the evaluation of leadership skills in student-athletes across different dimensions. These dimensions encompass modeling the way, encouraging the heart, enabling others to act, challenging the process, and inspiring a shared vision. Furthermore, this study investigates the level of involvement of student-athletes in academic sports diplomacy. This includes activities such as student-athlete exchanges, international sports competitions, cultural sports exchange programs, international sports projects, and cross-country competitions. The research emphasizes a positive relationship between leadership abilities and involvement in sports diplomacy initiatives, emphasizing the significance of leadership training in promoting active engagement. Furthermore, this study illuminates important challenges encountered by student-athletes, including limitations on time, gaps in awareness, the necessity for skill development, the juggling of competing priorities, the importance of cultural comprehension, and the significance of collaborative efforts. The results of this study provide valuable insights for the creation of strategies and programs that aim to empower student-athletes in their role as effective representatives of sports diplomacy. These initiatives seek to foster cultural connections and inspire positive global transformations.